Effect of step frequency on leg stiffness during running in unilateral transfemoral amputees - Hobara, Hiroaki (Sci Rep, 2020)
Spring-like leg behavior is a general feature of mammalian bouncing gaits, such as running and hopping. Although increases in step frequency at a given running speed are known to increase the stiffness of the leg spring (k(leg)) in non-amputees, little is known about stiffness regulation in unilateral transfemoral amputees. In this study, we investigated stiffness regulation at different step frequencies at a given running speed in unilateral transfemoral amputees. We recruited nine unilateral transfemoral amputees wearing running-specific prostheses. They were asked to perform the action of running across a range of step frequencies (±20, ±15, ±10, ±5, and 0% of their preferred step frequency) at a given speed on an instrumented treadmill. The k(leg) values were calculated using ground reaction force data in both the affected and unaffected limbs. It was found that k(leg) increased with increasing step frequency for the unaffected limb, but not for the affected limb. Consequently, the unilateral transfemoral amputees attained the desired step frequency in the unaffected limb, but were unable to match the three highest step frequencies using their affected limbs. These results suggest that the stiffness regulation strategy during running differs between the affected and unaffected limbs.